Case report of idiopathic cecal perforation presenting as acute appendicitis on ultrasound - Calista Harbaugh; Sabina Siddiqui; Cabrini Sutherland; Raja Rabah-Hammad; Ronald Hirschl (Elsevier, 2016)
Cecal perforation is an uncommon phenomenon in a pediatric population. It has been linked to a number of underlying medical conditions, which may result in focal inflammation or relative ischemia including hematologic malignancy, infection, and inflammatory bowel disease. We present an otherwise healthy 16-year-old male diagnosed with acute uncomplicated appendicitis on ultrasound, who was found to have cecal perforation with normal appendix intraoperatively, ultimately requiring ileocectomy. With this report, we aim to present the numerous pathophysiologic etiologies of cecal perforation, and to promote a comprehensive differential diagnosis despite the clinical and radiologic findings consistent with uncomplicated appendicitis.